Where is the Paraeducator Content in Introductory Special Education Textbooks? - Douglas, Sarah N.; Uitto, Denise J.; D'Agostino, Sophia (Journal of the American Academy of Special Education Professionals, 2021)
Paraeducators have become an important member of educational teams for students with disabilities. Although paraeducator supervision is mandated in federal law, numerous studies have noted challenges with paraeducator supervision. High quality teacher preparation, including use of materials that provide paraeducator focused content, is one way to ensure appropriate supervision and training of paraeducators. As a first step in analyzing teacher preparation materials for paraeducator content and alignment with research recommendations, a systematic review of introductory special education textbooks was conducted. Findings indicate limited content within most introductory special education textbooks regarding recommended team roles, professional standards, and paraeducator content. Limitations, future research directions, and implications for practice are discussed.